Effect of implant design and bone density in primary stability - Oliscovicz, Nathalia Ferraz; Shimano, Antônio Carlos; Junior, Elcio Marcantonio [UNESP]; Lepri, César Penazzo; Dos Reis, Andréa Cândido (FapUNIFESP (SciELO), 2013)
Aim: To evaluate the influence of the format and surface treatment of implants, as well as the substrate used in primary stability. Methods: Thirty-two Conexão® implants were used: 8 conical (CC) (11.5 x 3.5 mm) and 24 cylindrical (11.5 × 3.75 mm) - 8 external hexagon implants without surface treatment (MS), 8 external hexagon implants with double Porous treatment (MP), 8 internal hexagon implants with Porous treatment (CA). They were inserted in Nacional® polyurethane in three densities (15, 20 and 40 PCF). The insertion torque (IT) (N.cm) was quantified using the digital Mackena® torque meter, and the pullout force (PF) (N) by means of axial traction force with a 200 kg load cell, performed in a Universal Test Machine (Emic® DL-10000) and the Tesc 3.13 software. Data were analyzed statistically by ANOVA and Tukey's test with a significance level of 5%. Results: Difference was observed between groups (p<0.05). Regarding the IT, MP and MS inserted to the substrate 40PCF showed higher values with statistically significant difference with all interactions implants x substrate; the 15 and 20PCF densities was not significant in all groups of implants. MP, MS, CC and CA did not differ significantly, even inserted in a lower density, where CC showed better IT compared with other densities. For PF, the best performance was the interaction implant CA x 40PCF substrate, showing a difference from the other implants inserted in all substrates. Conclusions: The higher bone density and cylindrical implants with surface treatment provides greater IT and PF.
Keywords: Biomechanics; Bone substitutes; Dental implants; Polyurethanes